Morphological and Molecular identification of a new local strain of Eikenella corrodens isolated from chronic periodontitis - M. Salih, Mohammad; M. AL-Rawi, Amera (Medicinski časopis, 2024)
Objectives: This research focused on the morphological and molecular identification of a new local strain of Eikenella corrodens, which was isolated from 25 cases infected with chronic periodontitis. Methods: A modified Todd Hewitt agar medium was used for the first time locally to isolate the strain. The researchers then examined the isolate to determine its ability for slime layer production and formation of biofilm. Results: The results of the culture revealed that only one out of the twenty-five cases tested positive for Eikenella corrodens, accounting for a 4% occurrence. This positive result was further confirmed by PCR and gel electrophoresis. To identify the strain, the sequence of the 16S rRNA gene of E. corrodens was determined and compared with the existing data available at the National Center for Biotechnology Information (NCBI). The sequence was deposited in GenBank under the accession number OQ996282.1. The strain was named MeAm. Additionally, the researchers found that this particular isolate demonstrated a strong ability to form biofilm. Conclusion: These findings contribute to the understanding of the local strain of Eikenella corrodens and its characteristics in relation to chronic periodontitis, providing valuable insights for further research and potential treatment strategies.